2005
DOI: 10.1002/chin.200533200
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ferrocenylpyrazole Derivatives.

Abstract: Organo-iron compounds S 7100Synthesis of Ferrocenylpyrazole Derivatives. -The reactions of pyrazolines (II) and (VI) with aromatic aldehydes are studied aiming at the development of a convenient method for the synthesis of ferrocenylpyrazoles. The reaction of (II) and (VI) with aldehydes (III) and (VII) occurs as an intramolecular oxidation of the pyrazoline ring into pyrazole with concomitant reduction of an exocyclic functionality into the methylene group. Sufficiently high antiviral activities are shown by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…[4][5][6] The influence of the support on catalytic properties of hydroprocessing catalysts has been studied with great interest. [6][7][8] Many materials have been tested as supports to Mo and W active components with Co and Ni as promoters, some of which are SiO 2 , 9 MgO, 10 ZrO 2 , 11,12 TiO 2 , 13 carbon, 14 and mixed oxides such as TiO 2 -ZrO 2 , 15 [19][20][21] TiO 2 -SiO 2 , 22 etc. Zeolites such as NaY, 23,24 USY, 25 ZSM-5, 26 and β-zeolite 27 have also been employed as supports.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] The influence of the support on catalytic properties of hydroprocessing catalysts has been studied with great interest. [6][7][8] Many materials have been tested as supports to Mo and W active components with Co and Ni as promoters, some of which are SiO 2 , 9 MgO, 10 ZrO 2 , 11,12 TiO 2 , 13 carbon, 14 and mixed oxides such as TiO 2 -ZrO 2 , 15 [19][20][21] TiO 2 -SiO 2 , 22 etc. Zeolites such as NaY, 23,24 USY, 25 ZSM-5, 26 and β-zeolite 27 have also been employed as supports.…”
Section: Introductionmentioning
confidence: 99%
“…The pyrazolyl entity in 15 intersects with the adjacent ferrocenyls by 45.65(13) and 36.22(11)°, which is slightly larger than for the recently published N -benzyl derivative (26.5 and 29.4°) [ 60 ]. For the N -phenyl ( 15 ) and N -benzyl [ 60 ] pyrazoles, single and double bonds within the aromatic heterocycle could be distinguished ( Figure 6 ), contrary to the 1 H -derivative 13 . Therein, tautomerism causes a similar occupations for hydrogens to be placed at either of the pyrazole′s nitrogen atoms.…”
Section: Resultsmentioning
confidence: 75%
“…In this respect, it was found that ferrocenyl-functionalization of pyrazoles enhances their biological activities [ 55 , 56 , 57 , 58 , 59 ]. Facile synthesis methods of ferrocenyl-substituted pyrazoles were reported [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ], with only a brief comment about the parent diferrocenyl NH-pyrazole in 1963 [ 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…The previous synthesis of the bromodienone rac-3 was based on a bromination-elimination sequence of the saturated 40 dienone. 12 However, we found that the synthesis of bromodienone based on a bromination-elimination protocol developed for α,β-unsaturated ketones works better. Thus, in this way rac-3 was synthesized from dienone rac-2 in 65% yield.…”
Section: Synthesismentioning
confidence: 90%